Regulatory Mechanisms and Novel Therapeutic Targeting Strategies for Protein Tyrosine Phosphatases - Zhi-Hong Yu; Zhong‐Yin Zhang (2017)
An appropriate level of protein phosphorylation on tyrosine is essential for cells to react to extracellular stimuli and maintain cellular homeostasis. Faulty operation of signal pathways mediated by protein tyrosine phosphorylation causes numerous human diseases, which presents enormous opportunities for therapeutic intervention. While the importance of protein tyrosine kinases in orchestrating the tyrosine phosphorylation networks and in target-based drug discovery has long been recognized, the significance of protein tyrosine phosphatases (PTPs) in cellular signaling and disease biology has historically been underappreciated, due to a large extent to an erroneous assumption that they are largely constitutive and housekeeping enzymes. Here, we provide a comprehensive examination of a number of regulatory mechanisms, including redox modulation, allosteric regulation, and protein oligomerization, that control PTP activity. These regulatory mechanisms are integral to the myriad PTP-mediated biochemical events and reinforce the concept that PTPs are indispensable and specific modulators of cellular signaling. We also discuss how disruption of these PTP regulatory mechanisms can cause human diseases and how these diverse regulatory mechanisms can be exploited for novel therapeutic development.